Seasonal variation in infant mortality rates in the City of Salvador, BA, Brazil - Dias, Célia Guimarães Netto (Revista de Saúde Pública, 1975)
The seasonal variation of infant mortality in the city of Salvador was studied regarding the period 1962 to 1971, according to groups of causes, for the neonatal and post-neonatal ages. All death certificates of children less than a year old were revised. Seasonal variation indices were calculated using the method of chain relatives or relatives in chain. The highest seasonal indices of infant mortality in Salvador ocurred in general from February to July. This is possibly due to insatisfactory sanitation in association with increased rainfall during this period. The lowest seasonal indices ocurred from August to December.